Effects of trospium chloride on the lower urinary tract function - Suzuki, T (Hinyokika kiyo. Acta urologica Japonica, 1990)
The effects of trospium chloride on the lower urinary tract function were studied by combined recording of cystometry and sphincter electromyogram in 13 decerebrated dogs. Micturition was induced by bladder filling before and after drug administration. A statistical analysis was carried out on the urodynamic parameters. Trospium chloride at the dose of 0.1 mg/kg showed a small but significant decrease in the threshold pressure during the collecting phase. In the urodynamic parameters of the emptying phase which is considered to be influenced by cholinergic activity, there was a significant decrease in maximum bladder pressure at 0.03, 0.1, and 0.3 mg/kg and a significant increase in residual urine at 0.3 mg/kg. Trospium chloride is probably acting as a antimuscarinic agent in this study. Trospium chloride appears to be useful for the relief of symptoms associated with hyperactive bladder contraction